University students perceptions of the use of Know-Want-Learned (KWL) strategy in reading comprehension - Hermida, Rita (Accentia: Journal of English Language and Education, 2022)
This study investigates the English learners perceptions of the application of Know-Want-Learned (KWL) strategy in reading comprehension class. The study used the quantitative method, employing a questionnaire to collect the data needed. The respondents of the study were 30 students majoring in English Education at a public university in Banda Aceh, Aceh Province, Indonesia. The respondents had already experienced the use of KWL strategy in the Reading Comprehension class. The findings showed that and the students perception of KWL strategy was generally positive that most of them felt that KWL is suitable to use to help them in their reading comprehension on English texts.